Standarisasi Kinerja Waktu dan Biaya dengan Metode Earned Value pada Tahap Pekerjaan Struktur Proyek - Agitiya Wahyu , Andre; Gunasti , Amri; Cahya Dewi , Ilanka (Indonesian Journal Publisher, 2024)
The Jember Millennium Home Center Project experienced delays, because there was a difference between the costs that should have been spent not in accordance with the scheduled work performance and the difference here is negative. Therefore, research on cost index analysis and schedule performance index on the Jember Millennium Home Center project has no shortage of costs and the realization of completion work in the field is late. The purpose of this research is to calculate CPI and SPI. The method used in this research is Earned Value Analysis. The results showed that the Schedule Variant (SV) had a negative value of -Rp.30,940,091.57. While the value (CV) for 15 weeks has a positive value of Rp. 16,779,031.46, - from the difference in BCWP fees of Rp. 47,719,123 and ACWP Rp. 30,940,091, - means the project does not suffer losses.